Back to the Basics: Two Approaches for the Identification and Extraction of Lipid Droplets from Malassezia pachydermatis CBS1879 and Malassezia globosa CBS7966. Issue 5 (5th May 2021) - Mantilla, Maria Juliana; Cabrera Díaz, Catherine Eliana; Ariza‐Aranguren, Gabriela; de Cock, Hans; Helms, J. Bernd; Restrepo, Silvia; Jiménez, Elizabeth; Celis Ramírez, Adriana Marcela
Abstract: Malassezia spp. are lipid‐dependent yeasts that have been related to skin mycobiota and dermatological and systemic diseases. Study of lipid droplets (LDs) is relevant to elucidate the unknown role of these organelles in Malassezia and to gain a broader overview of lipid metabolism in Malassezia . Here, we standardized two protocols for the analysis of LDs in M. pachydermatis and M. globosa . The first describes co‐staining for confocal laser‐scanning fluorescence microscopy, and the second details extraction and purification of LDs. The double stain is achieved with three different neutral lipid fluorophores, namely Nile Red, BODIPY™ 493/503, and HCS LipidTOX™ Deep Red Neutral, in combination with Calcofluor White. For LD extraction, cell wall rupture is conducted using Trichoderma harzianum enzymes and cycles of vortexing with zirconium beads. LD purification is performed in a three‐step ultracentrifugation process. These standardizations will contribute to the study of the dynamics, morphology, and composition of LDs in Malassezia . © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Lipid droplet fluorescence staining Basic Protocol 2 : Lipid droplet extraction and purification Support Protocol : Malassezia spp. culture conditions